The potential of thin film nanocomposite membrane in reducing organic fouling in forward osmosis process - Emadzadeh, D. (Elsevier, 2014)
A major limiting factor of forward osmosis (FO) membrane, particularly in pressure retarded osmosis (PRO) mode, is fouling by natural organic matters. In this work, we investigated the effect of the nanocomposite substrate on the fouling of a thin film nanocomposite (TFN) membrane due to organic foulants in PRO mode. The TFN membrane was synthesized by coating a polyamide film over the surface of substrate made of polysulfone–titanium dioxide. The TFN membrane always showed much higher FO water flux than the typical thin film composite TFC membrane prepared from the pristine polysulfone substrate. Reduced internal concentration polarization following a significant decrease of the structural parameter in the nanocomposite substrate causes the mass transfer coefficient of the substrate to increase. In the PRO mode, BSA removal in the presence of Ca2 + confirmed that the TFN FO membrane could significantly mitigate fouling tendency compared to a typical TFC membrane. Results also showed that fouling in TFN FO is highly reversible, recovering > 92% permeate flux after a simple water rinse process. A complete study of the membrane fouling was reported with detailed scientific discussion. To the best of our knowledge, this is the first report on the effect of the nanocomposite membrane on membrane fouling in PRO mode.